Implementation of Economic and Fiscal Systems (Case Study of the Umayyad Period) - Yusri Karmila; Sabbar Dahham Sabbar; Muh.Fuad Randy; Tuti Supatminingsih (Faculty of Economics Merdeka University Surabaya Jl. Ketintang Madya VII/2 Karah, Kec. Jambangan, Kota SBY, Jawa Timur 60232, 2024)
During the Umayyad period, policies emerged in the form of development of the Islamic economic system in terms of stock trading, murabahah, muzara'ah, and the work of Al Kharaj. His government. This article uses a qualitative literature review approach by collecting data from a number of literature-based books, which will then be reviewed and processed to obtain appropriate findings. This technique is known as the documentation method.The results and discussion of the article are that during the Umayyad Daulah era, Islamic economic development policies emerged in the form of increasing economic growth and development, namely trade, agriculture and industry, fiscal reform and currency creation. The development of Islamic economic thought during the Umayyad Daulah period. During the reign of the 3 caliphates, namely the First Caliph Mu'awiyah Bin Abu Sofyan, he was able to implement progressive policies and bring success to the Muslim economy at that time. Mu'awiyah bin Abu Sofyan was a figure who was skilled at being an organizer and drafter, this skill was able to reduce the chaos at that time well, and was able to build a Muslim society with good order; The second caliph, Abdul Malik bin Marwan, during his leadership, policies included: 1. Currency Issuance 2. Postal Institutions 3. Restrictions on Urbanization 2 4. Agriculture 5. Trade 6. Kharaj and Zakat; The third caliph, Umar bin Abdul Aziz, during his leadership, policies included: 1. Eliminating discrimination 2. Zakat 3. Administration 4. Agriculture 5. Kharaj and Jizyah.